Insights into Cancer-Associated Thrombosis Leading Towards Ischemic Stroke - Surajit Hansda; Hiranmoy Das (Biology)
Stroke leads to significant disability in most patients, whereas cancer elevates the occurrence of stroke. The incidence of cancer-associated stroke (CAS) is projected to rise as a result of improvements in cancer therapies. Various forms of cancer have been demonstrated to be linked to ischemic stroke. Cancer might influence stroke pathophysiology either directly or through coagulation that creates a hypercoagulative state, in addition to infections. Treatment methods for cancer, including chemotherapy, radiotherapy, and surgery, have all been demonstrated to increase the risk of stroke as well. This review discusses the subtypes, epidemiology, pathophysiology, mechanisms of stroke within cancer patients, biomarkers, and signaling pathways of stroke in cancer while providing vital information on the involved transcription factors, treatment, and management of patients with cancer-associated ischemic stroke. Atherosclerosis, extracellular vesicles (EVs), and signaling biomolecules can also affect CAS. Overall, stroke is a significant and not uncommon complication of cancer, and there is an immediate demand for neurologists and oncologists to create strategies for screening and preventing strokes in cancer patients.